PENGARUH PERSEPSI KUALITAS PELAYANAN E-COMMERCE TERHADAP KEPUASAN PELANGGAN, KEPERCAYAAN DAN LOYALITAS PADA PRODUK FASHION - Oktania Setyaningsih (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2014)
The specifics goal of study are namely to explain the influence of (1) Quality of Service Satisfaction, (2) Service Quality of the Trust, (3) Service Quality to Loyalty (4) Satisfaction to Loyalty, and (5) of the Loyalty Trust. The population in this study are all consumers who had conducted the transaction in Saqina.com. The number of respondents was used a sample of 250 respondents.The population in this study are all consumers who had conducted the transaction in Saqina.com. The number of respondents was used a sample of 250 respondents. The results showed a significant effect of interaction between variables in the four effects, namely: (1) Quality of Service Satisfaction (CR = 5578), (2) Quality of Service Trust (CR = 5164), (3) Satisfaction to Loyalty (CR = 2009 ), (4) of the Loyalty Trust (CR = 2144), whereas no significant effect of the Service Quality to Loyalty (CR = -1766), calculation results also showed that the total effect of Trust is a mediating variable between Service Quality to Loyalty.As for the stimulus to do the marketing, among others, are (1) maintain a COD service to increase customer trust, (2) optimize customer satisfaction through improved service, the information presented better organized so that consumers more easily and comfortably in the transaction, (3) Provide a stage 'order tracking' for customers, so customers can monitor the extent to which the development of product orders. For future studies are expected to (1) Develop more variables studied, (2) Perform the comparison e-commerce both in Indonesia and internationally.